Pengaruh Perilaku Dan Komunikasi Terhadap Prestasi Kerja Agent Pada PT. Asuransi Allianz Cabang Merauke - Maria Kaok (Musamus University, Merauke Papua Indonesia., 2018)
This study aims to determine the effect of (1) behavior on agent work performance (2) the influence of communication on the work performance of agents (3) the influence of behavior and communication simultaneously on the work performance of agents at PT. Allianz Insurance Merauke Branch. The sampling technique used in this study was total sampling where all populations were sampled, namely 63 customers. Data analysis techniques used to solve the problems in this study were using multiple linear regression analysis. For significant tests with r test and test f. The results showed that the behavior had a positive and significant effect on agent work performance, communication had a positive and significant effect on the agent's work performance and behavior and communication also had a positive and significant effect on the agent's work performance. Keywords: Behavior, Communication, Work Performance.